If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x = 3 + -1x Solving 1x = 3 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 1x + x = 3 + -1x + x Combine like terms: 1x + x = 2x 2x = 3 + -1x + x Combine like terms: -1x + x = 0 2x = 3 + 0 2x = 3 Divide each side by '2'. x = 1.5 Simplifying x = 1.5
| 2x^3+x^2+6=0 | | -14+3(x+5)=7(2x+4)+x | | 3p^2(2p+1)=0 | | 8a^2-8=728 | | 5c+3=48 | | 9(6y-5)(2y+3)=0 | | x-139=81-9x | | y=22+9*-2 | | 12-2e=7e+8 | | 12x^2-3x-54=0 | | x=3x-50 | | E^8=2m+3 | | 20(y-4)-4(7y+8)=-16(y+4) | | 3x-y=-22 | | Ln(3x+5)=6 | | x^3-8x^2+32x-64=0 | | 8x-15=-15 | | 2x-y=-16 | | -m-6=3m+14 | | 2y^2-20y+45=x | | c=4n | | 6+8z=7z+4 | | 3x+9=27-9x | | a^2-a+156= | | 36-4g=8 | | -7n-5+2n-5(5n+1)=0 | | 4x+10=10-6x | | 3x-10=5x-10 | | 5+11x=95 | | (5+2i)+(3+6i)= | | q-5-2=7-q | | 12+2.4c=22.5 |